In Situ Ligand Bonding Management of CsPbI3 Perovskite Quantum Dots Enables High‐Performance Photovoltaics and Red Light‐Emitting Diodes - Shi, Junwei; Li, Fangchao; Jin, Yan; Liu, Cheng; Cohen‐Kleinstein, Ben; Yuan, Shuai; Li, Youyong; Wang, Zhao‐Kui; Yuan, Jianyu; Ma, Wanli (Angewandte Chemie International Edition, 2020)
To fine‐tune surface ligands towards high‐performance devices, we developed an in situ passivation process for all‐inorganic cesium lead iodide (CsPbI3) perovskite quantum dots (QDs) by using a bifunctional ligand, L‐phenylalanine (L‐PHE). Through the addition of this ligand into the precursor solution during synthesis, the in situ treated CsPbI3 QDs display significantly reduced surface states, increased vacancy formation energy, higher photoluminescence quantum yields, and much improved stability. Consequently, the L‐PHE passivated CsPbI3 QDs enabled the realization of QD solar cells with an optimal efficiency of 14.62 % and red light‐emitting diodes (LEDs) with a highest external quantum efficiency (EQE) of 10.21 %, respectively, demonstrating the great potential of ligand bonding management in improving the optoelectronic properties of solution‐processed perovskite QDs. A passivation process for all‐inorganic cesium lead iodide (CsPbI3) perovskite quantum dots (QDs) was developed by using a bifunctional ligand, L‐phenylalanine (L‐PHE). The in situ treated CsPbI3 QDs display significantly reduced surface states, increased vacancy formation energy, higher photoluminescence quantum yields, and much improved stability.